2019
DOI: 10.1136/bmjopen-2018-022553
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids injections versus corticosteroids with hyaluronic acid injections in rhizarthrosis: the randomised multicentre RHIZ’ART trial study protocol

Abstract: IntroductionOsteoarthritis of the trapeziometacarpal joint affects approximately 10%–25% of women, especially those who are postmenopausal. It may result in thumb dysfunction. Among the treatments, intra-articular injections of corticosteroid (CS) and hyaluronic acid (HA) are both effective and recommended. However, clinical trials have shown that HA improves functional capacity, whereas CS only produces a decrease in pain. The synergy of these two drugs has not been evaluated. The primary goal of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Interestingly, the protocol of a new randomized multicenter study, the RHIZ’ART trial, aimed to analyze, for the first time, the possible synergistic effect of corticosteroids associated with HA, compared to steroid alone, in TBOA patients, was published last year ( Cormier et al, 2019 ). The Authors would like to compare VAS pain, Cochin score, grip strength and opposition force, 3 months after a single injection of 0.5 ml of corticosteroid and 0.5 ml of physiological saline or 0.5 ml of corticosteroid and 0.5 ml of HA and would like to continue the follow-up until 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the protocol of a new randomized multicenter study, the RHIZ’ART trial, aimed to analyze, for the first time, the possible synergistic effect of corticosteroids associated with HA, compared to steroid alone, in TBOA patients, was published last year ( Cormier et al, 2019 ). The Authors would like to compare VAS pain, Cochin score, grip strength and opposition force, 3 months after a single injection of 0.5 ml of corticosteroid and 0.5 ml of physiological saline or 0.5 ml of corticosteroid and 0.5 ml of HA and would like to continue the follow-up until 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…23,26,27 Dexamethasone has been used therapeutically in inflammation, especially on the small joint, with its potent anti-inflammatory effects from the inhibition of the production and secretion of inflammatory cytokines such as interferon-gamma, interleukins, tumor necrosis factoralpha, and factor stimulating granulocytic and macrophage colonies. 28,29 Arthrocentesis is another valuable method to improve TMJ symptoms and promote healing of the TMJ by the lavage of the development of a traumatic condition. 4 Other than these clinical studies, no clear evidence has been reported to support the necessity and efficacy of intervention for the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…11 Corticosteroids have been used therapeutically in the inflammation of different joints, showing positive results in small joints, such as the trapeziometacarpal. 12 Corticosteroids are one of the tools used in the management of TMJ internal disorders, generating the best anti-inflammatory effect due to the inhibition of the production and secretion of proinflammatory cytokines such as interleukins, tumour necrosis factor alpha, interferon gamma and factor stimulating granulocytic and macrophage colonies by direct interference on cascades and genomic mechanisms. They also inhibit the accumulation of macrophages and neutrophils in inflammatory foci because they repress the expression of endothelial adhesion molecules and the synthesis of the plasminogen activator.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Corticosteroids have been used therapeutically in the inflammation of different joints, showing positive results in small joints, such as the trapeziometacarpal. 12 …”
Section: Introductionmentioning
confidence: 99%